Peningkatan Kompetensi Bahasa Inggris Guru PAUD melalui Workshop Microteaching Berbasis Storytelling - Nurmayana Nurmayana; Margaret Stevani; Nurhalimah Nurhalimah; Linda Astuti Rangkuti (Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to improve early childhood education (ECE) teachers' competence in teaching English through a storytelling-based workshop and microteaching. The activity was conducted at PAUD Terpadu Princess, Rokan Hilir, involving five teachers. The methods included delivering Teaching English to Young Learners (TEYL) materials, developing theme-based lesson plans (RPPH), and teaching practice. Data were collected via pre-tests, post-tests, observations, and perception questionnaires. Results showed a significant increase in teachers' cognitive abilities, with the average score rising from 53.0 to 87.0 (gain score +34). Microteaching assessments averaged 17.2 (Good category), with storytelling techniques being the strongest aspect. The perception questionnaire scored 4.5 (Very Good), indicating the training was beneficial and relevant. In conclusion, hands-on practice and guided feedback are effective in enhancing pedagogical skills for teaching English. This program is recommended for regional replication and sustainable development.